HIV-1 gp120 Determinants Proximal to the CD4 Binding Site Shift Protective Glycans That Are Targeted by Monoclonal Antibody 2G12 - Clapham, Paul R.; Dueñas Decamp, María José (ASM, 2010)
HIV-1 R5 envelopes vary considerably in their capacities to exploit low CD4 levels on macrophages for infection and in their sensitivities to the CD4 binding site (CD4bs) monoclonal antibody (MAb) b12 and the glycan-specific MAb 2G12. Here, we show that nonglycan determinants flanking the CD4 binding loop, which affect exposure of the CD4bs, also modulate 2G12 neutralization. Our data indicate that such residues act via a mechanism that involves shifts in the orientation of proximal glycans, thus modulating the sensitivity of 2G12 neutralization and affecting the overall presentation and structure of the glycan shield.